Suspension acoustics an introduction to the physics of suspensions - Temkin, Samuel 1936- (Cambridge University Press, 2005)
Originally published in 2005, this book is an introduction to the physics of suspensions of bubbles, droplets, and solid particles in both gases and fluids. Rather than treating each combination separately, a unified approach is used that permits most particle-fluid combination types to be discussed together. To do this, the book first presents a detailed discussion of the basic particle motions that small particles can sustain, paying particular attention to translations and pulsations, and to the thermal effects that occur as a result of those motions. The book then introduces the reader to the dynamics and thermodynamics of suspensions, with acoustic motions providing the main focus in the latter part of the book. The important acoustic problems of attenuation and dispersion are discussed from several fundamental perspectives. The book concludes with applications of acoustic techniques to the characterization and modification of suspensions by means of acoustic waves